Interactions between Plant and Mineral Additives in Ruminant Nutrition: Opportunities for Integration And Challenges of Use: Article Review - Hassan, Shahla Fathola; musa Albayati, Husham jaafar (American Journal of Biodiversity, 2025)
Source additive—plant extracts such as essential oils, condensed tannins, saponins, and other polyphenols—are expected to offer reductions in enteric methane output by ruminants; the same applies for mineral additives like Zn, Cu, Se, and Co, which are required for antioxidant defense against free radicals production through energy metabolism or vitamin B12 synthesis. Combining both additive classes would allow complementary effects to be exploited: for example, phytochemicals with a stimulatory effect on the redox capacity and rumen microbiomes can modulate tannins or sulfides in protected mineral carriers by ensuring that bioavailability is not compromised. Field data yields feed conversion improvements from 3 to 6%, milk selenium enrichment of up to 60%, and methane reductions ditching in on the downside of ≥10% where doses are optimized, well balanced with an encapsulation enhancing temperature loss or chelation. Yet, those same responses can have negative effects—excessive binding of Cu and Zn by tannins, depressed palatability due to high essential oil contents—while nano mineral toxicokinetics are understudied. Precision feeding particularly relies on an integrated dose-response model, routine blood or liver-based diagnostics, and manure management plans limiting soil Cu/Zn accumulation. Ultimately, long-term cross-disciplinary trials that include microbiome analysis and climate-corrected forage mineral profiles are required to improve safe upper limits of DMI while maintaining productivity with environmental stewardship.